2021
DOI: 10.1530/rep-20-0392
|View full text |Cite
|
Sign up to set email alerts
|

Functional attributes of seminal proteins in bull fertility: a systematic review

Abstract: Proteomic approaches have been widely used in reproductive studies to uncover protein biomarkers of bull fertility. Seminal plasma is one of the most relevant sources of these proteins that may influence sperm physiology. Nonetheless, there are still gaps in existing knowledge in the functional attributes of seminal proteins. Thus, we reviewed the relationships between seminal plasma proteins and bull fertility by conducting a systematic review with data obtained from 71 studies. This review showed that the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 66 publications
1
13
0
Order By: Relevance
“…Comprehensive sperm protein databases have been established for a plethora of species, including insects, avian, ruminants, porcine, equine, or human [ 11 , 32 , 34 , 62 , 63 , 64 , 65 ]. The sperm proteome covers the expected spectrum of function (from energy production to cell recognition), but few proteins are accurately linked to (in)fertility [ 66 ]. The seminal fluid proteome, even in species lacking all accessory sexual glands as in avian species [ 64 , 65 ], depicts clear phylogenetic relevance for fertility for its direct relation to sperm function, mechanisms of energy production/consumption, proteolysis and oxidoreduction.…”
Section: The Composition Of the Seminal Plasma: Comparative Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comprehensive sperm protein databases have been established for a plethora of species, including insects, avian, ruminants, porcine, equine, or human [ 11 , 32 , 34 , 62 , 63 , 64 , 65 ]. The sperm proteome covers the expected spectrum of function (from energy production to cell recognition), but few proteins are accurately linked to (in)fertility [ 66 ]. The seminal fluid proteome, even in species lacking all accessory sexual glands as in avian species [ 64 , 65 ], depicts clear phylogenetic relevance for fertility for its direct relation to sperm function, mechanisms of energy production/consumption, proteolysis and oxidoreduction.…”
Section: The Composition Of the Seminal Plasma: Comparative Aspectsmentioning
confidence: 99%
“…However, differences in type and source of proteins are present among species, owing to the already named differences in glands and/or the sequence they are emptied, or the type of ejaculate they have. Comparative studies [ 63 ] have shown particular roles played by SP proteins in ruminants amply used for AI, holding single ejaculates [ 66 , 69 , 72 , 73 ], but also in species—including humans—with fractionated ejaculates, where the proteome type, concentration and temporal exposition are relevant [ 11 ].…”
Section: The Composition Of the Seminal Plasma: Comparative Aspectsmentioning
confidence: 99%
“…The fertilizing capacity of a male is influenced by sexual behaviour, endocrinology, genetics, and sperm intrinsic and extrinsic factors (Butler et al, 2019; Kastelic & Thundathil, 2008; Rodriguez‐Martinez et al, 2021). While intrinsic factors include sperm features, such as morphology, motility, concentration, and membrane integrity, extrinsic factors are related to non‐cellular components of semen capable of modulating sperm functional attributes (Evans et al, 2020; Özbek et al, 2020; Viana et al, 2021). Seminal plasma is one of these extrinsic factors.…”
Section: Introductionmentioning
confidence: 99%
“…Significant variations in fertility scores, sperm parameters, and sperm freezability of bulls relate to dissimilarities in the proteome of seminal fluid (Fouchécourt et al, 2002; Gomes et al, 2020; Jobim et al, 2004; Kasimanickam et al, 2019; Killian et al, 1993; Moura et al, 2006, 2007; Rego et al, 2016; Viana et al, 2018; Willforss et al, 2021). However, our recent systematic review found substantial asymmetry among the results published in those studies due to variations in methods of protein analysis, bovine breeds, semen collection, sperm endpoints, and sample storage conditions (Viana et al, 2021). Moreover, proteins associated with fertility parameters were tested in cause‐and‐effect experiments, which helped to confirm (or not) the empirical link detected between seminal protein and bull fertility (Viana et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation